The molecular mechanism research of cartilage calcification induced by osteoarthritis. Issue 5 (2nd May 2022) - Jiang, Shilin; Zhang, Chengyuan; Lu, Ye; Yuan, Feng
ABSTRACT: To explore the molecular mechanism of cartilage calcification induced by osteoarthritis (OA) based on distal-less homeobox gene 5 – alkaline phosphatase – integrin-binding sialoprotein – ecto-nucleotide pyrophosphatase 1 (DLX5-ALPL-IBSP-ENPP1) signal axis. Twenty-four rabbits were selected to build models of cartilage calcification induced by OA and randomly divided into 3 groups. The first group was the normal group whose rabbits were injected into 0.9% saline (0.3 mL), and the second group was model group. The third group was model group whose rabbits were injected into DLX5 antibody by caudal vein. Alizarin red calcium staining was used to analyze calcium deposition of cartilage matrix. Immunohistochemical staining was used to analyze the relative expression levels of proteins DLX5 and ENPP1, and western blot was used to analyze the DLX5, ALPL, IBSP, and ENPP1 expression. Calcium salt precipitation was the most serious, and the calcification area increased in the model group. Although calcified nodules appeared in the anti-DLX5 group, they were relatively few. Immunohistochemical staining analysis showed that the protein DLX5 located in the nucleus and the protein ENPP1 located in the extracellular matrix. Western blot analysis showed that the expressions of proteins DLX5, ALPL, IBSP, and ENPP1 were the highest in OA Model group than that of NC group, followed by anti-DLX5 group. The proteins DLX5, ALPL, IBSP, and ENPP1 can promote cartilage calcification induced by OA based on DLX5-ALPL-IBSP-ENPP1 signal axis.